2014
DOI: 10.4049/jimmunol.1302108
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: An Antibody Recognizing Ancestral Endogenous Virus Glycoproteins Mediates Antibody-Dependent Cellular Cytotoxicity on HIV-1–Infected Cells

Abstract: The failure of antiviral vaccines is often associated with rapid viral escape from specific immune responses. In the past, conserved epitope or algorithmic epitope selections, such as mosaic vaccines, have been designed to diversify immunity and to circumvent potential viral escape. An alternative approach is to identify conserved stable non–HIV-1 self-epitopes present exclusively in HIV-1–infected cells. We showed previously that human endogenous retroviral (HERV) mRNA transcripts and protein are found in cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…We, and others, have previously shown that HERV-K (HML-2) can be reactivated in HIV infection [ 26 28 ]. The mechanisms leading to HERV-K (HML-2) expression are still being elucidated, but HIV Vif and Tat proteins have been implicated [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…We, and others, have previously shown that HERV-K (HML-2) can be reactivated in HIV infection [ 26 28 ]. The mechanisms leading to HERV-K (HML-2) expression are still being elucidated, but HIV Vif and Tat proteins have been implicated [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms involved in the activation of endogenous retroviruses and their role in immune activation should be the subject of additional investigations. The development of interventions directed at the prevention of the activation of other endogenous retroviruses suggests that the characterization of endogenous retrovirus activation in bipolar depression may eventually lead to novel therapeutic interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Distinguishing differences in the surface phenotype of cells from elite controllers of HIV compared with 'non-controllers' may provide a window for how viral infection can be controlled naturally, which could be used to design more effective strategies. Nixon and coworkers identified ancestral endogenous retroviral proteins that have been measured on the surface of infected HIV cells within 'elite controllers', and an antigen-specific T-cell response by HEV-K (HML-2)-specific T cells triggered a CTL response, as well as antigen-specific antibody for mediating a humoral response against HIV-infected cells makes the human endogenous retrovirus a promising target to consider for immunotherapy [83].…”
Section: Considerations For Future Developmentmentioning
confidence: 98%